A comparative study of serum electrolytes in newborns with birth asphyxia and non-asphyxiated newborns - Dr. Manjunatha Babu R; Dr. Pavan Kumar Jerry; Dr. Harish G; Dr. Susheela C (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Birth asphyxia is a common neonatal problem and contributes significantly to neonatal morbidity and mortality. HIE is the foremost concern in asphyxiated neonate because contrary to other system derangements this has the potential to cause serious long term neuromotor sequel among survivors.Sodium, potassium and calcium are the major electrolytes in human body, and any deviation from their normal levels in blood might cause convulsions, shock and other metabolic abnormalities. Immediate aggressive treatment of these abnormalities could modify the entire outcome of the babies.Methods: The study was a case control study conducted over a period of 2years. Case (asphyxiated) group comprised of term babies weighing 2.5 kg or more with birth asphyxia. Birth asphyxia was said to be present in those babies who had a definite APGAR score of less than 7 at 1 minute of birth. Control (non-asphyxiated) group was made up of term babies weighing 2.5 kg or more with APGAR scores of 7 or more at 1 minute of birth. Blood samples collected were immediately sent to the biochemistry lab for evaluation of serum sodium, potassium and calcium.Results: A total of 100 newborn babies were included in the study, 50 babies in case group and 50 babies in control group. Mean serum sodium and calcium values were significantly lower in the asphyxiated group when compared to the non-asphyxiated group. Mean serum potassium was significantly higher in the asphyxiated group when compared to the non-asphyxiated group. The mean serum sodium and calcium values in severely asphyxiated babies were significantly lower when compared to mild/moderately asphyxiated babies and the non-asphyxiated group.Conclusions: As serum sodium levels are low in birth asphyxia, fluids must be managed judiciously in asphyxiated newborns.